Representasi Tokoh Perempuan dalam Film Black Panther: Wakanda Forever - Yulis Nila Sari (Jurnal Ilmu Komunikasi, 2021)
The film Black Panther: Wakanda Forever places women as the main characters in the film. Princess Shuri is described as a tomboyish woman, without make-up, with short hair, and has a brave, strong and intelligent character. This central depiction of a female character shows an alternative side of femininity where women are no longer seen as weak. The unique presentation of female characters in this film attracts the attention of researchers to find out more about the representation of female characters. Not only Shuri's character is the focus of research but other figures such as the Wakandan warrior. In conducting the analysis the researcher uses a qualitative description method with the aim of explaining the results of the study. While the theory used is Roland Barthes' semiotics who wants to know the meaning of denotation, connotation, and signs in films. Through the research that has been carried out, it has resulted in findings that the second Black Panther film makes women the main superhero characters, which have changed the myths of beauty and women in patriarchal culture. Beauty is no longer constructed by meeting standard beauty myths such as white skin color and long hair. Women are also no longer portrayed as following a patriarchal culture where women are the number two figure. Women in this film are described as having the same strength as men so that there is equality in them. In addition, the film Wakanda Forever tends to present masculine dominance in female characters. It can be seen through the depiction of characteristics such as physique, personality and behavior of female characters.